SHARIA SERVICES WITH A LEVEL OF PATIENT SATISFACTION IN HOSPITALS: LITERATURE REVIEW - Rizqon, Muhamad Syofwan; Sulisno, Madya; Suryawati, Chriswardani (Jurnal Keperawatan Respati Yogyakarta, 2020)
Satisfaction is an expression of someone's pleasure from the results of a comparison between perceptions or products that are perceived as expected. Satisfied patients will tend to reuse hospital services and patients will leave the hospital if they feel  dissatisfied. Sharia services in the field of nursing are services provided by nurses based on quran and hadith that can improve patient satisfaction at the hospital. The aim of this paper is to identify how the relationship of sharia services in the field of nursing with the level of patient satisfaction and identify the patient's knowledge of sharia services to take the decision to get care at the hospital. The method used is the review literature from pubmed. scientdirect.google scholar.Portal Garuda. Articles with English and Indonesian with restrictions on publishing articles from 2010-2019. There is a significant relationship between sharia services and the level of patient satisfaction at the hospital. The better the sharia service provided, the more patient satisfaction will be. It is hoped that there will be more discussion and study between the Islamic Hospital and the Government Hospital so that the form of sharia services can be applied in all hospitals throughout Indonesia.